A Case Study On Golden Hope Plantations Berhad - Ibrahimy, Ahmad Ibn (2003)
In order to provide a better understanding of various aspects of plantation industry in Malaysia, a study is undertaken on Golden Hope Plantations Berhad. The study is divided into two parts; Part One gives an overview of Golden Hope Plantations Berhad while Part Two provides the case analysis on Golden Hope.